The Influence of Principal Managerial and Teacher Competence on Class Management Ability in Elementary School Environment - Freza Sapta Derie; Bukman Lian; Muhammad Juliansyah Putra (Yayasan Sembilan Pemuda Indonesia, 2027)
This study aims to analyze the influence of the principal's managerial competence and teachers' competence on classroom management skills in public elementary schools in Banyuasin III District. A quantitative approach with a survey method was employed. The sample comprised 35 teachers selected through saturated sampling. Data were collected using questionnaires and documentation. Analysis utilized descriptive statistics, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). Findings indicate that the principal's managerial competence has a positive and significant effect on teachers' classroom management skills. Similarly, teachers' competence exerts a positive and significant effect on classroom management skills. Simultaneously, both variables demonstrate a positive and significant effect, confirming that they jointly predict effective classroom management. This study provides empirical evidence from a district-level elementary school context in Banyuasin III, demonstrating the combined predictive power of principal and teacher competencies on classroom management in an under-researched rural setting. Findings underscore the need for school administrators and district policymakers to invest in targeted professional development programs that strengthen both principal managerial capacity and teacher pedagogical competence to optimize classroom management outcomes. This research contributes actionable insights for educational stakeholders, affirming that classroom management effectiveness is substantially enhanced when leadership competence and teaching competence are developed synergistically, offering a foundational reference for capacity-building strategies in similar elementary education contexts.